New directions for research in foreign language education - Coffey, Simon; Wingate, Ursula (Routledge, Taylor & Francis Group, 2018)
New Directions for Research in Foreign Language Education brings together contributions by reputed scholars that examine the challenges, opportunities, and benefits of teaching and learning foreign languages. With a particular focus on languages other than English, the book looks at the socio-political dimension of language learning and teaching and the need to re-theorize multilingualism for our age. The volume includes a range of perspectives, from language teaching as an act of reconciliation to language learning across the lifespan, from innovations in assessment and curriculum to critical appraisals of pedagogy and textbook materials. Each chapter presents a clear case study drawn from diverse contexts to illustrate the different concerns of the contributors. The book is a valuable resource for all students, teachers, teacher educators and researchers who share an interest in researching multilingualism and the different facets of teaching and learning foreign languages.